Who Benefits from State and Local Economic Development Policies? - Bartik, Timothy J. (W.E. Upjohn Institute, 1991)
Bartik reviews evidence on whether state and local policies affect job growth. He then presents empirical data supporting the intentions of such programs, showing that job growth may lead to a number of positive long-term effects including: lower unemployment, higher labor force participation, higher real estate values, and better occupational opportunities. He also shows that the earnings gains to disadvantaged groups outweigh the resulting increased real estate values for property owners, and concludes by saying that regional competition for jobs may actually be a benefit for the nation as a whole. He also introduces the Bartik Instrument.